ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMA N 5 KOTA JAMBI MELALUI PEMBELAJARAN BERBASIS MASALAH PADA KONSEP PENCEMARAN LINGKUNGAN - Adek Fujika; Evita Anggereini; Retni Sulistyoning Budiarti (BIODIK, 2015)
ABSTRACT. The purpose of this study was to analyze the students' critical thinking skills through problem-based learning on the concept of an environmental pollution in the city of Jambi SMAN 5 academic year 2015/2016. This research is a descriptive study. The study was conducted on 2 January to 25 February 2015. The research subjects were selected using random sampling techniques as many as 40 students from class X MIA 7. Data is collected using observation sheets, sheet questionnaires, and interviews. This study describes the results of observation sheets, the results of the questionnaire and interview sheet. Overall average high school students' critical thinking skills N 5 Jambi through problem-based learning on the concept of environmental pollution is high. The results obtained from the five indicators critical thinking skills which gives a simple explanation was obtained by 77% of the analytical results of observation, and 83% of the results of questionnaire analysis. Indicators build basic skills gained as much as 77% of the analytical results of observation and 81% of the results of questionnaire analysis, concluded indicator gained as much as 81% of the analytical results of observation and 82% of the results of questionnaire analysis. Indicators provide further explanation was obtained by 82%, from the analysis of observation, and 83% of the results of questionnaire analysis. Indicators set the strategy and tactics gained as much as 81% of the analytical results of observation and 84% of the results of questionnaire analysis. Results of interviews with teachers show that the learning process biology students have used critical thinking skills. Conclusions from this research is the critical thinking skills of students during learning activities in this study in the category of high ability.